Fresno County Bar Association's Annual Judges' Dinner at Bob Crossland's Barn - Watkins, Howard::::::::: (1982)
Charles Oren, Judge James V. Paige on drums, Robert Oliver on trumpet, and Truman Campbell on clarinet